Exploring the mediating role of psychological capital: the impact of authentic leadership and perceived organisational toward organisational citizenship behaviour - Apriliana, Gabriella; Hartijasti, Yanki (Universitas Negeri Surabaya, Indonesia, 2024)
This study aims to investigate the impact of psychological capital on the effect of authentic leadership and perceived organisational support on employee organisational citizenship behaviour (OCB). Despite having at least one year of experience in the private sector, employees display OCB that does not align with the organisation's expectations. The evolving nature of work suggests that simply assessing employees' relationships with the organisation may not be sufficient. Instead, employees' relationships with supervisors and perceived organisational support should be a consideration. Additionally, employees must possess a strong intrinsic motivation to tackle work-related challenges effectively. This study employed the Partial Least Square-Structural Equation Modelling (PLS-SEM) method and included 275 permanent employees from the private sector. Data was collected using Google Forms, and the analysis was conducted using SmartPLS 4 software. The findings indicate that psychological capital mediates the relationship between authentic leadership, perceived organisational support, and OCB. This study implies that organisations can cultivate a workplace environment that nurtures psychological capital, strengthens authentic leadership, and enhances perceived organisational support. Consequently, employees will be more likely to exhibit OCB that aligns with organisational expectations, leading to improved overall performance and workplace harmony.